“We Are Seneca Lake”: Defining the Substances of Sustainable and Extractive Economics Through Anti-Fracking Activism - Murphy, Mollie K. (Frontiers in Communication, 2020)
Scholars of environmental communication have had difficulty discerning whether and how nature should be considered as an economic resource for humans. This article examines how strategic definitions of environmental substance can forward a rhetorical vision of sustainable economics. Turning to a successful anti-fracking campaign, it illustrates the definitional means through which activists challenge fossil fuel dependence with an ecological perspective of economic and environmental health. Contextual, nutritive, and directional substance in New York’s “We Are Seneca Lake” campaign together constitute the Finger Lakes’ local economy as a blueprint for a sustainable future. This article contributes to scholarship and advocacy at the intersections of environmental activism and industry rhetoric.